Consuming places - Urry, John (International library of sociology., 2002)
John Urry has been discussing and writing on these and similar questions for the past fifteen years. In Consuming Places, he gathers together his most significant contributions. Urry begins with an extensive review of the connections between society, time and space. The concept of 'society', the nature of 'locality', the significance of 'economic restructuring', and the concept of the 'rural', are examined in relationship to place. The book then considers how places have been transformed by the development of service occupations and industries. Concepts of the service class and pos.